2022
DOI: 10.3389/fnins.2022.830820
|View full text |Cite
|
Sign up to set email alerts
|

Is Mate Preference Recognizable Based on Electroencephalogram Signals? Machine Learning Applied to Initial Romantic Attraction

Abstract: Initial romantic attraction (IRA) refers to a series of positive reactions toward potential ideal partners based on individual preferences; its evolutionary value lies in facilitating mate selection. Although the EEG activities associated with IRA have been preliminarily understood; however, it remains unclear whether IRA can be recognized based on EEG activity. To clarify this, we simulated a dating platform similar to Tinder. Participants were asked to imagine that they were using the simulated dating platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…However, our results showed a contrast in alpha frontal asymmetry, in which there was a relatively higher right frontal activity in the no-choice phase. For the beta and gamma frequency bands, there was a relatively higher frontal asymmetry during the “choice” conditions, which was in line with previous research that relates higher left frontal beta activity compared to right frontal activity to consumers’ purchase decisions ( Aftanas et al, 2006 ; Ramsøy et al, 2018 ; Zhao et al, 2018 ; Alarcão and Fonseca, 2019 ; Lin et al, 2021 ; Yuan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, our results showed a contrast in alpha frontal asymmetry, in which there was a relatively higher right frontal activity in the no-choice phase. For the beta and gamma frequency bands, there was a relatively higher frontal asymmetry during the “choice” conditions, which was in line with previous research that relates higher left frontal beta activity compared to right frontal activity to consumers’ purchase decisions ( Aftanas et al, 2006 ; Ramsøy et al, 2018 ; Zhao et al, 2018 ; Alarcão and Fonseca, 2019 ; Lin et al, 2021 ; Yuan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have found that the preferences of marriageable individuals towards potential romantic partners is associated with a decrease in the power of alpha and beta frequency bands [7], as well as an increase in the amplitude of LPP and P300 [8]. Based on these findings, Yuan et al (2021) extracted relevant features from EEG signals and conducted research on romantic interest recognition using a random forest classifier, with an average classification accuracy of 85.2% [9].…”
Section: Introductionmentioning
confidence: 99%